What Makes Cities Attractive? The Determinants of Urban Labour Migration in Germany. (July 2014) - Buch, Tanja; Hamann, Silke; Niebuhr, Annekatrin; Rossen, Anja
Striking disparities characterise the population growth of cities in industrialised countries. Some cities suffer from ongoing population decline, whereas other cities have experienced increasing numbers of inhabitants in recent years. Whether labour market conditions or amenities via their impact on migration primarily account for differences in cities' demographic development is an important issue. This paper investigates the determinants of the migration balance of German cities between 2000 and 2007. The focus is on the mobility of workers because labour migration in particular affects the future prospects of cities. The findings suggest that not only labour market conditions but also amenities have an impact on the net migration rate. Moreover, large cities seem to be, ceteris paribus, more attractive than small cities. This finding possibly points to the importance of amenities such as cultural infrastructure and matching externalities in urban (labour) markets that are linked to city size. Urban policy aimed at enhancing the attractiveness of cities should thus consider both boosting the local economy and improving the quality of life.